Maternal Exposure to Iodine Excess Throughout Pregnancy and Lactation Induces Hypothyroidism in Adult Male Rat Offspring - Serrano-Nascimento, Caroline (Sci Rep, 2017)
This study aimed to investigate the consequences of maternal exposure to iodine excess (IE; 0.6 mg NaI/L) throughout pregnancy and lactation on the hypothalamus-pituitary-thyroid axis of the male offspring in adulthood. Maternal IE exposure increased hypothalamic Trh mRNA expression and pituitary Tsh expression and secretion in the adult male offspring. Moreover, the IE-exposed offspring rats presented reduced thyroid hormones levels, morphological alterations in the thyroid follicles, increased thyroid oxidative stress and decreased expression of thyroid differentiation markers (Tshr, Nis, Tg, Tpo, Mct8) and thyroid transcription factors (Nkx2.1, Pax8). Finally, the data presented here strongly suggest that epigenetic mechanisms, as increased DNA methylation, augmented DNA methyltransferases expression, hypermethylation of histone H3, hypoaceylation of histones H3 and H4, increased expression/activity of histone deacetylases and decreased expression/activity of histone acetyltransferases are involved in the repression of thyroid gene expression in the adult male offspring. In conclusion, our results indicate that rat dams’ exposure to IE during pregnancy and lactation induces primary hypothyroidism and triggers several epigenetic changes in the thyroid gland of their male offspring in adulthood.